PENGARUH PRODUKTIVITAS TENAGA KERJA TERHADAP TINGKAT UPAH PADA PENGOLAHAN INDUSTRI KOPRA (STUDI KASUS DI DESA RUMBA-RUMBA KABUPATEN KONAWE SELATAN) - Samrin, Samrin (JIDE : Journal Of International Development Economics, 2022)
This research was conducted in Rumba-rumba Village, South Konawe Regency, the problem in this research is the effect of labor productivity on wage levels in Rumba-rumba Village. The purpose of this study was to determine and analyze the effect of labor productivity on the level of wages in Rumba-rumba Village. The analytical method used is simple regression, with a total sample of 25 people. The results showed that the effect of labor productivity had a positive and significant effect on the level of wages. The simple regression formula equation can be obtained as follows: 0.735 (Y) = 0.746 (X1). Based on Table 4.9 above, it shows that the regression coefficient value of the labor productivity variable (b1) is positive, namely 0.746, meaning that for every 1 unit increase in labor productivity, it will increase the wage rate by 0.746 units assuming the other independent variables have a fixed value. Based on the data above, it shows that the Adjusted R2 value is 0.457 indicating that the wage level variable (Y) can be explained by the independent variable in the form of labor productivity (X1) or its value is 45.7 percent and the remaining 54.3 percent is explained by other variables outside this research model.